Dissolution P and K of leucite and apatite rocks using a combination of humic compounds-PhSB-PSB - Mohammad Jimmy Kurnianta (Menara Perkebunan, 2019)
Due to the limited availability of potassium and phosphate in soil and the high price of their synthetic mineral fertilizers, the importance of minerals-solubilizing microorganisms has been increasingly significant aimed at sustainable agriculture achievement. Apatite and leucite are considerably abundant minerals; however, their solubility is low. This study was aimed to study the effects of the combination of phosphate-and potassium-solubilizing bacteria (PhSB and PSB) and humic acid of cassava as bioleaching agents in the solubilization process of potassium and phosphate from agromineral material. Some leucite agromineral materials were obtained from Situbondo and Pati, while apatite materials were obtained from Tuban and Ciamis, Indonesia. The minerals were treated with 2.10 x 107 CFU/g PhSB and 1.61 x 107 CFU/g PSB isolates, combined with 100 ppm organic C humic compounds from cassava as the media. The minerals solubility was monitored every two weeks for 12 weeks of observation, which includes the concentration of dissolved K and P, as well as the pH of the media. The presence of organic acids was observed to monitor the bacterial activity by using HPLC, while the physical changes of the rock surface due to bacterial dissolution were scanned by using scanning electron microscopy (SEM). The results showed that the highest dissolution of P was recorded at week 4 (344.23 ppm) released from Tuban apatite with the combination of PhSB and PSB under the humic compound. In contrast, the highest K dissolution was obtained at week 6 for Situbondo leucite (44.21 me/100 g) with a combination of humic cassava compound and PSB only. Statistical analyses showed a mark different on both minerals for dissolution of K and P. The SEM result indicates breakage of the rock surface after a three month observation period indicating that the dissolution minerals occurred. Selected organic acids such as citric, ferulic, coumaric, syringic, and malic acids were detected during the treatment.